A novel stibacarbaborane cluster with adjacent antimony atoms exhibiting unique pnictogen bond formation that dominates its crystal packing - Holub, Josef; Melichar, Petr; Růžičková, Zdeňka; Vrána, Jan; Wann, Derek A; Fanfrlík, Jindřich; Hnyk, Drahomír; Růžička, Aleš (Dalton transactions (Cambridge, England, 2017)
We have prepared nido-7,8,9,11-Sb2C2B7H9, the first cluster with simultaneous Sb-B, Sb-C and Sb-Sb atom pairs with interatomic separations with magnitudes that approach the respective sums of covalent radii. However, the length of the Sb-Sb separation in this cluster is slightly less than the sum of the covalent radii. Quantum chemical analysis has revealed that the crystal packing of nido-7,8,9,11-Sb2C2B7H9 is predominantly dictated by pnictogen (Pn) bonding, an unconventional σ-hole interaction. Indeed, the interaction energy of a very strong Sb2H-B Pn-bond in the nido-7,8,9,11-Sb2C2B7H9 dimer exceeds -6.0 kcal mol-1. This is a very large value and is comparable to the strengths of known Pn-bonds in Cl3Pnπ complexes (Pn = As, Sb).